The Intention of Young Muslim Generation to Use the Islamic E-Wallet Services in Indonesia - Handi Risza (ETIKONOMI, 2024)
Research Originality: Technological developments have changed human behavior in economic activities, including payment methods that use e-wallets. On the other hand, consumers also need an e-wallet that complies with Sharia principles. The COVID-19 pandemic forced consumers to use digital payment methods. However, the number of studies related to the continued usage of Islamic e-wallets in Indonesia remains limited.Research Objectives: Hence, our study examines the factors influencing a person's intention to use an Islamic e-wallet.Research Method: The theoretical framework used in this study is the Technology Acceptance Model. The analysis technique employed is multiple regression analysis using 371 respondents.Result: Empirical results indicate that the factors influencing a person's intention to use an Islamic e-wallet are usability, ease of use, trustworthiness, and religiosity. However, the risk variable does not significantly affect a person's intention to use an Islamic e-wallet. Implication: These results imply that companies must improve the features and services of Islamic e-wallet applications.JEL Classification: D10, G29How to Cite:Risza, H. (2024). The Intention of Young Muslim Generation Using the Islamic E-wallet Services in Indonesia. Etikonomi, 23(1), 219 – 232. https://doi.org/10.15408/etk.v23i1.37452.